Efektifitas Metode Pembelajaran Discovery Learning Pada Proses Pembelajaran Sosiologi Di SMA Negeri 1 Maros Sebagai Optimalisasi Pemahaman Konsep Sosiologi - Novia Damayanti; Agung Indra Wijaya; Muhammad Nawir (Institut Nalanda, 2024)
The sociological learning process is very worrying in class XI IPS at SMAN 1 MAROS. This is caused by many things, such as the large number of students playing during the lesson. Therefore, teachers have a role to provide understanding to students, of course by applying appropriate learning methods. One learning method that can be used by teachers is the discovery learning method. Next, research was conducted at SMAN 1 MAROS to determine the effectiveness of the Discovery Learning method in providing students with an understanding of sociological concepts. Classroom action research (CAR) is a type of research in which teachers work together to improve class performance and student learning outcomes by planning, implementing, and thinking about what will be done. A total of 30 students in class XI IPS 1 UPT SMA Negeri 1 Maros were the subjects of this research. Classroom action research was conducted in two cycles, with four meetings per cycle, which included six learning process meetings and two meetings for learning outcomes tests. The sociology learning outcomes of class XI IPS 1 UPT SMA Negeri 1 Maros students can be improved by using the Discovery Learning Model. According to observations of student attitudes during classroom action research in cycle I and cycle II, the application of the Discovery Learning Model can increase the frequency of activeness and activity in the teaching and learning process.